The development of measurement instruments of Sharia students' perceptions about Khilafah - Subando, Joko; Wibowo, Muhammad Kurniawan Budi; Farkhani, Farkhani (REID (Research and Evaluation in Education), 2023)
This study aims to develop an instrument to measure Sharia students' perception of the Khilafah. The research applied the ADDIE development research approach. The activity began with reviewing Taqiyuddin An-Nabhani's books and articles about Khilafah to get the instrument construct (analysis). The next stage was to compile the grid and assemble the instrument items (design). The items of the assembled instrument were then assessed by 11 experts (development). The validated Instruments were then carried out with limited and expanded trials. The limited trial was conducted on 26 students at Universitas Islam Negeri (UIN) Salatiga, and the expanded trial was conducted on 227 Sharia students from Institut Islam Mamba'ul "˜Ulum (IIM) Surakarta, UIN Raden Mas Said, and UIN Salatiga. The experimental data were analyzed with CFA. The results indicate that the instrument construct consisted of seven aspects of measurement encompassing the essence, the function, the establishment, the power and sovereignty, the form of state and government, the Khilafah government system, and the constitution for non-Muslims. The measurement model meets eight model fit criteria, including AGFI = 0.84 (> 0.8), chi-square/df = 1.459 (< 2), RMR = 0.054 (â‰¤ 0.1), SRMR = 0.056 (â‰¤ 0.1), RMSEA = 0.045 (< 0.08), NFI = 0.95 (â‰¥ 0.9), NNFI = 0.98 (â‰¥ 0.9), CFI = 0.98 (â‰¥ 0.9), IFI = 0.98 (â‰¥ 0.9). The instrument also has a good guarantee of validity and reliability. This is indicated by the loading factor value of each indicator above 0.4 and the composite reliability value of 0.95 (> 0.7) so that the instrument can be used for further measurements.